ANALISIS AKURASI PENERAPAN SOFTWARE AUDACITY DALAM MENENTUKAN NILAI FREKUENSI PADA PRAKTIKUM PIPA ORGANA - Alya Orkins Fitriyani; Febby Andryani (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
An organ pipe is a tool that uses an air column to produce sound. This research on organ pipes has the main goal, namely to determine the resonant frequency produced from each tone. The working principle of this research is to move the piston to produce the highest tone. The frequency obtained from manual calculations is in accordance with the existing theory, where the frequency and pipe length are inversely proportional. The relative frequency error in Audacity Software with the calculation results shows a small number, namely 1.08%, which means that the result has a high degree of accuracy.